Regulatory governance of the water sector in South Africa - Muller, Kobus (Philippine Journal of Public Administration, 2003)
Among the many challenges inherited by South Africa in 1994, one of the more difficult and pressing relates to provision of adequate water services to almost a third of the urban South African population which did not have access to potable water and sanitation facilities at that time; this number was even higher in the rural areas of the country. South Africa is a water-stressed country; thus water planners and managers are faced with an increasingly set of complex issues. This study focuses on the policy, legal and institutional framework as regards water supply, provision and regulation; access and economic issues; quality and standards; and the political context and its influence on the water sector, as it specifically relates to poverty in the post-1994 South Africa. An attempt is made to list some of the current and emerging issues in the regulatory governance of the water sector.